(untitled) (Asian Journal of Medical Sciences, 2014)
Pleomorphic adenoma is a benign tumor of salivary gland. Controversy regarding the origin of various mesenchymal components exists and myoepithelial cell has a key role. Metaplastic process is triggered by minor trauma and probable etiology for this change is ischemia. It is diagnostically challenging, because diagnostic pit falls in the presence of mucinous and squamous metaplasia. Report a case of pleomorphic adenoma in the palate of a 35 years old Indian female. Biopsy revealed epithelial component with extensive squamous metaplasia and cystic degeneration. Here we discuss the role of myoepithelial cells in the pathogenesis of pleomorphic adenoma and diagnostic pit falls. DOI: http://dx.doi.org/10.3126/ajms.v5i4.10434 Asian Journal of Medical Sciences 2014 Vol.5(4); 108-110